The Sociological Perspectives in Case Study: Empowering Student Capability based Law in Action Method in Indonesia Legal Education - Rayi Kharisma Rajib; Soultan Athar; Careno Bafaleo (The Indonesian Journal of International Clinical Legal Education, 2019)
Lack of application of law by the students in the life, is a problem that must be addressed immediately. The law is not just a "Law in Books", but must also "Law in Actions", Law in reality. And this is where the sociology of law plays an important role in making them. This paper will examine how the sociological perspective to strengthen the capacity of students based on the method of Law in Action in Education Law in Indonesia. As well as reviewing about the sociological perspective in legal education, sociology of clinical legal education, a variety of cases that occurred in the sociology of law and social law research. students have significant potential as a leading fighter in the change of the Indonesian nation. But not a few students who do not understand their true responsibilities. And also do not know, understand and practice the Tri Dharma Perguruan Tinggi which is a unity that cannot be separated, because the obligation of a student not only learn on campus for just science, but he has obligations that must be borne in accordance with Tri Dharma Perguruan Tinggi .